A prospective randomized controlled trial on the value of prophylactic oral nutritional supplementation in locally advanced nasopharyngeal carcinoma patients receiving chemo-radiotherapy. (December 2020) - Huang, Shuang; Piao, Yongfeng; Cao, Caineng; Chen, Jia; Sheng, Wei; Shu, Zekai; Hua, Yonghong; Jiang, Feng; Hu, Qiaoying; Chen, Xiaozhong; Chen, Yuanyuan
Highlights: A prospective prophylactic nutrition intervention study on NPC patients. New prospective evidence: Prophylactic ONS can decrease the delay of radiotherapy and increased the compliance of concurrent chemotherapy. Abstract: Objectives: We investigated the effect of prophylactic oral nutrition supplements (ONS) in locally advanced nasopharyngeal carcinoma patients receiving neoadjuvant chemotherapy and concurrent chemoradiotherapy (CCRT). Methods: Eligible patients were randomly assigned to an intervention or control group. Patients in the intervention group were supported with prophylactic ONS from the beginning of CCRT. The control group received nutritional support only when necessary. Bodyweight, hematological indexes, nutritional status, and quality of life were measured at baseline and before, during, and after RT. Results: We evaluated 114 patients from October 2016 to May 2018. More than half of patients experienced significant weight loss during CCRT, which continued for three months after radiotherapy (RT). Compared to baseline, the rate of weight loss ≥ 5% before, during, at the end of RT, and one and three months after RT were 3.5%, 28.9%, 51.8%, 61.4%, and 61.4%, respectively. Nutritional status and global health status scores progressively decreased during treatment. The rate of RT interruption was higher in the control group than in the intervention group (7.14% vs. 0%, χ 2  = 4.29, P = 0.04). More patients experienced concurrent chemotherapy interruption in the control group than in the intervention group (28.57% vs 10.34%, χ 2  = 6.08, P = 0.01). There were no significant differences in weight loss, nutritional status, quality of life, and global health status between two groups. Conclusions: Malnutrition and weight loss progressively increased during treatment. Prophylactic ONS can improve tolerance to CCRT, but it offers no advantage on short-term weight loss or nutritional assessment scores.